Experimental investigation of energy absorption behaviour of circular carbon/epoxy composite tubes under quasi-static and dynamic crush loading. (1st November 2019) - Liu, Xing; Belkassem, Bachir; Jonet, Arnaud; Lecompte, David; Van Hemelrijck, Danny; Pintelon, Rik; Pyl, Lincy
Abstract: Carbon/epoxy composites demonstrate significant and promising improvements of the weight-to-performance ratio in the automotive industry. In this paper, their energy absorption performance is thoroughly investigated. Quasi-static and dynamic axial crush tests have been performed on a variety of carbon/epoxy composite tube specimens with different thicknesses, layups and architectures (fabric and unidirectional). It is shown that the frequency response of the drop weight test setup bias the crush load histories and give false peak crush loads which lead to a wrong understanding of the elastic behaviour of the composites. Different filtering processes are adopted to investigate their necessity and influence on the energy absorption performance of carbon/epoxy composites. Comparing the specific energy absorption and crush efficiency of the variety of carbon/epoxy composite tube specimens, the fabric ones perform better than the unidirectional ones. The results show that more energy can be absorbed in the quasi-static conditions.